Characterization of brevilaterins, multiple antimicrobial peptides simultaneously produced by Brevibacillus laterosporus S62-9, and their application in real food system. (August 2021) - Ning, Yawei; Han, Panpan; Ma, Junmei; Liu, Yangliu; Fu, Yunan; Wang, Zhixin; Jia, Yingmin
Abstract: Multiple antimicrobial peptides (designated brevilaterin) were extracellularly produced by Brevibacillus laterosporus S62-9, five brevilaterins were purified by liquid chromatography, and characterized by MALDI-TOF/TOF MS and 2D-NMR. The results suggested that brevilaterin A-E (Mw 1568.9753, 1555.0334, 1601.0044, 1569.0189, 1583.0946 Da) showed similar primary structures exhibiting small variation of three amino acid substitutions at residue 3, 5, 7. Every brevilaterin contained a fatty acid (2-hydroxy-3-methylpentanoic acid) at the N -terminus and 13 amino acids including three modified amino acids: 2-amino-2-butenoic acid, ornithine and C -terminal residue of valinol, of which brevilaterin D was a new compound. Brevilaterins showed broad antimicrobial activities against bacteria and fungi, and were resistant to heat (retained over 80% antimicrobial activity at 121 °C for 20 min) and pH (no significant loss at pH 2 to 12). They effectively killed Staphylococcus aureus in milk. Collectively, these findings evidenced a promising application of brevilaterins in food preservation. Highlights: Five AMPs were extracellularly produced by Brevibacillus laterosporus. The primary structures of brevilaterins were purified and elucidated by 2D-NMR. Brevilaterins showed broad antimicrobial spectrum and good resistance to heat and pH. Brevilaterins showed promising application potential in food preservation.